1994
DOI: 10.1007/bf00696457
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of alkane oxidation byPseudomonas oleovorans

Abstract: Many Pseudomonads are able to use linear alkanes as sole carbon and energy source. The genetics and enzymology of alkane metabolism have been investigated in depth for Pseudomonas oleovorans, which is able to oxidize C5-C12 n-alkanes by virtue of two gene regions, localized on the OCT-plasmid. The so-called alk-genes have been cloned in pLAFR1, and were subsequent analyzed using minicell expression experiments, DNA sequencing and deletion analysis. This has led to the identification and characterization of of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
228
1
12

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(246 citation statements)
references
References 95 publications
5
228
1
12
Order By: Relevance
“…A membrane-bound alkane hydroxylase was first discovered in a hexane-degrading fluorescent pseudomonad tentatively named Pseudomonas oleovorans [39,40], but later identified as a P. putida [41]. Biochemical studies showed that the P. putida alkane hydroxylase system consists of an integral membrane monooxygenase [42][43][44], 1 or 2 rubredoxins [45][46][47], and a rubredoxin reductase [48,49] (Fig.…”
Section: Diversity Of Alkane Hydroxylase Systemsmentioning
confidence: 99%
“…A membrane-bound alkane hydroxylase was first discovered in a hexane-degrading fluorescent pseudomonad tentatively named Pseudomonas oleovorans [39,40], but later identified as a P. putida [41]. Biochemical studies showed that the P. putida alkane hydroxylase system consists of an integral membrane monooxygenase [42][43][44], 1 or 2 rubredoxins [45][46][47], and a rubredoxin reductase [48,49] (Fig.…”
Section: Diversity Of Alkane Hydroxylase Systemsmentioning
confidence: 99%
“…However, microorganisms capable of utilizing these compounds as only energy source can be found almost everywhere, even in non-contaminated sites [28,29].…”
Section: Biodegradation Of Alkanesmentioning
confidence: 99%
“…Even though several studies have shown that the alkB genes are widespread in nature [166], only the Pseudomonas putida GPo1 alkane hydroxylase system [167] has been studied in detail with respect to enzymology, genetics, as well as potential applications [28,167,168]. The alkane hydroxylase system of GPo1 consists of three components: a particulate hydroxylase (AlkB), which is the catalytic component localized in the cytoplasmic membrane, and two soluble proteins, rubredoxin (AlkG) and rubredoxin reductase (AlkT) ( Fig.…”
Section: Alkb In Pseudomonas Putida Gpo1mentioning
confidence: 99%
See 1 more Smart Citation
“…Many bacterial species play an active role in the process of petroleum fuel biodegradation. Some biodegradable hydrocarbons such as n-alkanes are known to be utilised by a large number of microorganisms as a sole source of carbon and energy 29,[53][54][55] . Polycyclic aromatic hydrocarbons and cyclo-alkanes are mainly degraded by co-oxidation in the environment 56 .…”
Section: Bioremediation: Why ? and How ?mentioning
confidence: 99%